Ecotechnalogy for Coastal Development of Port Sector - Ozasa, Hiroaki (PROCEEDINGS OF CIVIL ENGINEERING IN THE OCEAN, 1994)
Study results of ecotecnology for coastal development are introduced. The first result is an analysis of relation between annual maximum significant wave height in front of port structures and sessile organisms (sessile animals, motile organisms, and sea algae). The second result is a report of a mesocosm experiment of tidal flat. Ecological environment of the mesocosm and activities of benthos were studied.